BFO Theory with Variable Profit in Case of Advance Payments of Tax on Profit - Brusov, Peter; Filatova, Tatiana; Kulik, Veniamin (Journal of Reviews on Global Economics, 2023)
The Brusov–Filatova–Orekhova (BFO) theory is generalized for the simultaneous account of variable company profit and advance tax on income payments. The generalized BFO formula for the WACC, has been derived. The dependence of WACC, discount rate, WACC–g (here g is growth rate), company capitalization, V, the equity cost, ke, on leverage L at various values of g, on debt cost, kd, and on age of the company, n, is studied. It is shown, that WACC, is no longer a discount rate. This role passes to WACC–g, which decreases with g, while the company’s value increases with g. The tilt of curve k(L) growths with g. It is found that at the growth rate g < g* the tilt of the curve ke(L) is negative. This changes significantly the company’s dividend policy principles. WACC(L) as well as the discount rate, WACC–g, decrease with the increase of debt cost kd. V (L) at all values of kd increases with leverage L, as well V(L) increases with kd. This means that tax shield advantages the decrease of the cost of raising capital. Examining the main financial parameters of the company at the positive (g=0.2) and negative (g=–0.2) growth rates, we found a huge difference in their behavior. This allows you to explore companies with growing profits and companies with decreasing profits, as well investigate the financial state of the companies whose profits rise and fall in different periods.